2007
DOI: 10.1094/cchem-84-1-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ground Corn Particle Size on Ethanol Yield and Thin Stillage Soluble Solids

Abstract: The effects of ground corn particle size on ethanol yield and soluble solids in thin stillage was evaluated using a 2‐L laboratory dry‐grind procedure. The procedure was optimized for grinding, liquefaction, sacchari‐fication, and fermentation parameters. The optimized procedure was reproducible with a coefficient of variation of 3.6% in ethanol yield. Five particle size distributions of ground corn were obtained using a cross‐beater mill equipped with five screens (0.5, 2, 3, 4, and 5 mm). Particle size had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
4
29
2
Order By: Relevance
“…6 EVect of mash viscosity on ethanol fermentation eYciency particles by DSC, which likely inXuenced the completeness of starch hydrolysis resulting in lower fermentation eYciency for the larger particles. Several other researchers have reported similar results: for example, ethanol yield from Wnely ground (0.5-mm sieve) corn meal was 2.2% (v/v) higher than that from coarsely ground (5-mm sieve) meal, representing a »20% gain [25]. Therefore, ethanol plants should grind the feedstock grain as Wne as possible, balanced by grinding costs and avoidance of downstream process issues.…”
Section: Particle Size Of Ground Sorghum Mealmentioning
confidence: 57%
“…6 EVect of mash viscosity on ethanol fermentation eYciency particles by DSC, which likely inXuenced the completeness of starch hydrolysis resulting in lower fermentation eYciency for the larger particles. Several other researchers have reported similar results: for example, ethanol yield from Wnely ground (0.5-mm sieve) corn meal was 2.2% (v/v) higher than that from coarsely ground (5-mm sieve) meal, representing a »20% gain [25]. Therefore, ethanol plants should grind the feedstock grain as Wne as possible, balanced by grinding costs and avoidance of downstream process issues.…”
Section: Particle Size Of Ground Sorghum Mealmentioning
confidence: 57%
“…Previous investigations have demonstrated that the particle size distribution had an effect on fermentation yields. Naidu et al (2007) found that final ethanol concentrations increased as the granulation of ground maize was finer. A 22% increase in ethanol concentration was observed as the grinding screen size decreased from 5 to 0.5 mm.…”
Section: Resultsmentioning
confidence: 97%
“…Dien et al (2002) and VanCauwenberge et al (1982) used sequential saccharification and fermentation, methods not used in industry. Naidu et al (2007) developed a 500-g procedure for corn; a smaller scale procedure is needed that uses enzymes, yeast, and conditions similar to industry practice. Naidu et al (2007) developed a 500-g procedure for corn; a smaller scale procedure is needed that uses enzymes, yeast, and conditions similar to industry practice.…”
mentioning
confidence: 99%